Distributed Representations of Lexical Sets and Prototypes in Causal Alternation Verbs - Edoardo Maria Ponti; Bernardo Magnini; Elisabetta Jezek (IJCoL)
Lexical sets contain the words filling an argument slot of a verb, and are in part determined by selectional preferences. The purpose of this paper is to unravel the properties of lexical sets through distributional semantics. We investigate 1) whether lexical set behave as prototypical categories with a centre and a periphery; 2) whether they are polymorphic, i.e. composed by sub-categories; 3) whether the distance between lexical sets of different arguments is explanatory of verb properties. In particular, our case study are lexical sets of causative-inchoative verbs in Italian. Having studied several vector models, we find that 1) based on spatial distance from the centroid, object fillers are scattered uniformly across the category, whereas intransitive subject fillers lie on its edge; 2) a correlation exists between the amount of verb senses and that of clusters discovered automatically, especially for intransitive subjects; 3) the distance between the centroids of object and intransitive subject is correlated with other properties of verbs, such as their cross-lingual tendency to appear in the intransitive pattern rather than transitive one. This paper is noncommittal with respect to the hypothesis that this connection is underpinned by a semantic reason, namely the spontaneity of the event denoted by the verb.